A Domino Heck Coupling–Cyclization–Dehydrogenative Strategy for the One-Pot Synthesis of Quinolines - Ghora, Santanu; Sreenivasulu, Chinnabattigalla; Satyanarayana, Gedu (Synthesis, 2021)
An efficient, one-pot, domino synthesis of quinolines via the coupling of iodoanilines with allylic alcohols facilitated by palladium catalysis is described. The overall synthetic process involves an intermolecular Heck coupling between 2-iodoanilines and allylic alcohols, intramolecular condensation of in situ generated ketones with an internal amine functional group, and a dehydrogenation sequence. Notably, this protocol occurs in water as a green solvent. Significantly, the method exhibits broad substrate scope and is applied for the synthesis of deuterated quinolines through a deuterium-exchange process.
Keywords: quinolines; palladium catalysis; Heck coupling; deuterated quinolines; iodoanilines